Pengembangan Personal Branding Berbasis Website untuk Meningkatkan Identitas Profesional Siswa SMK AL-HASRA - Iqbal Muthahhary; Agung Siswopranoto; Brian Ridho Martani; Dimas Aditia Saputra; Lintan Zhuliani; Muhammad Fahri Assidqi; Muhammad Teva Syawal; Narendra Al’Abidin; Refliani Marsela; Yogi Adi Saputra; Robben Ahmad Hafiz (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology requires vocational high school (SMK) students to have a professional identity that can be displayed online as part of their readiness to enter the workforce. However, many SMK students still do not understand the concept of personal branding and do not have a representative digital portfolio. This article aims to analyze the effectiveness of Community Service (PkM) activities in the form of website-based personal branding development training in improving the digital literacy and professional identity of Al-Hasra SMK students. The methods used were socialization, training, and direct mentoring, with data collection techniques through observation, pre-test and post-test questionnaires, and activity documentation. The results of the activity showed a significant increase in students' understanding of personal branding and their ability to present their potential, skills, and experience professionally through websites. It was concluded that website-based personal branding training is effective as a strategy to strengthen the digital identity and work readiness of vocational school students. These findings have implications for the development of an applicable digital literacy training model for vocational education.